The effect of combined resisted agility and repeated sprint training vs. strength training on female elite soccer players - Shalfawi, S. A. I.; Haugen, T.; Jakobsen, T. A.; Enoksen, E.; Tonnessen, E. (The Journal of Strength and Conditioning Research, 2013)
The aim of this study was to compare the effects of in-season combined resisted agility and repeated sprint training with strength training on soccer players' agility, linear single sprint speed, vertical jump, repeated sprint ability (RSA), and aerobic capacity. Twenty well-trained elite female soccer players of age ± SD 19.4 ± 4.4 years volunteered to participate in this study. The participants were randomly assigned to either the agility and repeated sprint training group or to the strength training group. All the participants were tested before and after a 10-week specific conditioning program. The pretest and posttest were conducted on 3 separate days with 1 day of low-intensity training in between. Test day 1 consisted of squat jump (SJ), countermovement jump (CMJ), and RSA. Test day 2 consisted of a 40-m maximal linear sprint and an agility test, whereas a Beep test was conducted on test day 3 to assess aerobic capacity. The agility and repeated sprint training implemented in this study did not have a significant effect on agility, although there was a tendency for moderate improvements from 8.23 ± 0.32 to 8.06 ± 0.21 seconds (d = 0.8). There was a significant (p < 0.01) and moderate-positive effect on Beep-test performance from level 9.6 ± 1.4 to level 10.8 ± 1.0, and only a trivial small effect on all other physical variables measured in this study. The strength training group had a positive, moderate, and significant (p < 0.01) effect on Beep-test performance from level 9.7 ± 1.3 to level 10.9 ± 1.2 (d = 1.0) and a significant (p < 0.05) but small effect (d = 0.5) on SJ performance (25.9 ± 2.7 to 27.5 ± 4.1 cm). Furthermore, the strength training implemented in this study had a trivial and negative effect on agility performance (d = -0.1). No between-group differences were observed. The outcome of this study indicates the importance of a well-planned program of conditioning that does not result in a decreased performance of the players, the great importance of strength and conditioning specialist in implementing the training program, and the importance of choosing the time of the year to implement such conditioning training programs. However, the fact that the present training program did not cause any decline in performance indicates that it is useful in maintaining the soccer players' physical performance during the competition period.